Hubungan Pola Asah, Asih, dan Asuh dengan Kejadian Stunting di Wilayah Kerja Puskesmas Lontar Surabaya - Nur Astri Amelia (Media Gizi Kesmas, 2023)
Background: Stunting, often known as short children, is a condition in which a child's length or height is significantly below average for his or her age. Meeting children's basic needs throughout their formative years is an effective way to stop them from being stunted. Parents, and especially mothers, are responsible for seeing to their children's basic requirements. Developmental outcomes for toddlers are influenced by maternal involvement in caregiving. These fundamental requirements take the form of kindness, concern, and attention. Objectives: The purpose of this study was to analyze the relationship between the pattern of nurturing, caring and caring provided by mothers and caregivers with the incidence of stunting in the working area of the Lontar Health Center in Surabaya. Methods: This study used a case-control design, making it an analytical observational study. A total of 52 children took part in the study, and they were split evenly between two groups (the "case" group included 26 kids, while the "control" group had 26 kids) (not stunted). Purposive sampling was utilized to gather these samples. The acquired data was put through a battery of statistical tests, and the findings were analyzed using the Chi-square technique. Results: The results of the study showed that there was a significant relationship between mother's knowledge (p=0.041) and patterns of breastfeeding related to the implementation of IMD (p=0,048) and the incidence of stunting. Conclusions: The conclusion obtained from this study is that mother's knowledge and implementation of IMD are related to the incidence of stunting.